2005
DOI: 10.1021/jm050015d
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Evaluation of Ruthenium(II)−Arene PTA Complexes

Abstract: The antitumor activity of the organometallic ruthenium(II)-arene complexes, RuCl(2)(eta(6)-arene)(PTA), (arene = p-cymene, toluene, benzene, benzo-15-crown-5, 1-ethylbenzene-2,3-dimethylimidazolium tetrafluoroborate, ethyl benzoate, hexamethylbenzene; PTA = 1,3,5-triaza-7-phosphaadamantane), abbreviated RAPTA, has been evaluated. In vitro biological experiments demonstrate that these compounds are active toward the TS/A mouse adenocarcinoma cancer cell line whereas cytotoxicity on the HBL-100 human mammary (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
700
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 747 publications
(741 citation statements)
references
References 61 publications
26
700
1
4
Order By: Relevance
“…Among them, a series of arene-ruthenium complexes such as RM175, RAPTA-C, RAED-C, and UNICAM-1 have shown very promising therapeutic effects. [8][9][10][11][12] Additionally, a class of cyclometalated ruthenium complexes known as RDCs (ruthenium-derived compounds) has shown particularly good activity as anticancer agents, for both in vitro and in vivo studies. [8,13] Various reports have shown that the mechanisms by which phenylpyridine derivatives exert their anticancer effects are presumably not through DNA interaction, as in the case of cisplatin, but in part through redox reactions with oxidoreductases.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, a series of arene-ruthenium complexes such as RM175, RAPTA-C, RAED-C, and UNICAM-1 have shown very promising therapeutic effects. [8][9][10][11][12] Additionally, a class of cyclometalated ruthenium complexes known as RDCs (ruthenium-derived compounds) has shown particularly good activity as anticancer agents, for both in vitro and in vivo studies. [8,13] Various reports have shown that the mechanisms by which phenylpyridine derivatives exert their anticancer effects are presumably not through DNA interaction, as in the case of cisplatin, but in part through redox reactions with oxidoreductases.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] They have gained widespread attention since two complexes, namely NAMI-A and KP1019 (and the respective sodium salt KP1339), passed early clinical trials. [19][20][21] The use of ruthenium in PDT however, has been quite limited so far.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, ruthenium(II)-arene complexes bearing 1,3,5-triaza-7-phosphaadamantane (pta) ligands-named 'RAPTA' [7]-have been found to exhibit promising antimetastatic properties in vivo, and appear to function in a way different from cisplatin. [8][9][10] Indeed, ruthenium complexes could prove to be effective alternatives to those based on platinum, and trans-[tetrachloro(dimethyl sulphoxide)(imidazole) ruthenate(III)] (NAMI-A) [11] and trans-[tetrachlorobis (1H-indazole)ruthenate(III)] (KP1019) [12] have both completed phase I clinical trials.…”
Section: Introductionmentioning
confidence: 99%